Enantiospecific pharmacokinetics of intravenous dexmedetomidine in beagles. Issue 4 (29th April 2022) - Levionnois, Olivier Louis; Barbarossa, Andrea; Bardhi, Anisa; Siegenthaler, Joelle; Forss Pleyers, Tekla; Guidi, Monia; Spadavecchia, Claudia; Raillard, Mathieu
Abstract: The goal of this study was to investigate the pharmacokinetic (PK) behaviour of dexmedetomidine in dogs administered as a pure enantiomer versus as part of a racemic mixture. Eight unmedicated intact purpose‐bread beagles were included. Two intravenous treatments of either medetomidine or dexmedetomidine were administered at 10‐ to 14‐day intervals. Atipamezole or saline solution was administered intramuscularly 45 min later. Venous blood samples were collected into EDTA collection tubes, and the quantification of dexmedetomidine and levomedetomidine was performed by chiral LC–MS/MS. All dogs appeared sedated after each treatment without complication. Plasma concentrations of levomedetomidine were measured only in the racemic group and were 51.4% (51.4%–56.1%) lower than dexmedetomidine. Non‐compartmental analysis (NCA) was performed for both drugs, while dexmedetomidine data were further described using a population pharmacokinetic approach. A standard two‐compartment mammillary model with linear elimination with combined additive and multiplicative error model for residual unexplained variability was established for dexmedetomidine. An exponential model was finally retained to describe inter‐individual variability on parameters of clearance (Cl1 ) and central and peripheral volumes of distribution (V1, V2 ). No effect of occurrence, levomedetomidine or atipamezole could be observed on dexmedetomidine PK parameters. Dexmedetomidine did not undergo significantly different PK when administered alone or as part of the racemic mixture in otherwise unmedicated dogs.